BOOK CHAPTER PEMBERIAN TERAPI KOMPLEMENTER BAGI IBU POSTPARTUM - Dwi Kurniawati (2021)
Complementary therapy for postpartum mothers is useful in improving the quality of mother's comfort, reducing anxiety and giving mothers a handle to get through the days after giving birth. The provision of complementary therapy can not only be carried out by nurses, but also by families, especially husbands who will always accompany mothers through difficult times after giving birth and improve their welfare.